THE ROLE OF FREE RADICAL OXIDATION IN THE DEVELOPMENT OF CONTRAST-INDUCED DISORDERS OF RENAL FILTRATION - N. T. Vatutin; M. I. Zinkovych; E. D. Yakubenko (Архивъ внутренней медицины)
Aim. To find out the links between the state of system and the risk and severity of impairment of renal function in patients after percutaneous coronary intervention (PCI).Material and methods. The free radical oxidation system’s response was assessed in patients with different degree of severity of the glomerular filtration impairment. The intensity of lipid peroxidation was evaluated by the concentration of malondialdehyde (MDA) in the red blood cells of patients.Results. Almost all 59 patients after PCI were observed with various degree of inhibition of renal filtration. The mean value of MDA significantly (p = 0,032) increased from 10,3 ± 1,7 mmol/g to 11,0 ± 1,8 mmol/g. The level of MDA was significantly higher (p <0,001) in the group of patients with more severe inhibition of glomerular filtration.Conclusion. The results indicate the important role of free radical processes in the pathogenesis of renal function impairment.